PERTIMBANGAN HAKIM DALAM MEMUTUS PEMIDANAAN TERDAKWA ANAK DALAM KASUS TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN - Seno Satrio Heryadi; Muhammad Rustamaji (Verstek, 2025)
This research in legal writing aims to examine the judge's considerations in giving a criminal decision in a criminal case of theft with aggravating circumstances in decision number: 2/Pid.Sus-Anak/2024/PN SKH. who imposed a prison sentence of 4 (four) months based on Article 363 paragraph (1) 4th and 5th of the Criminal Code concerning Aggravated Theft and Based on Article 183 and Article 184 of the Criminal Procedure Code. This research is prescriptive normative legal research. The approach used is the case approach, the case approach is an approach carried out by examining cases that relate to legal issues and have received a decision by a judge that has permanent legal force. Legal materials are obtained from primary and secondary legal materials. The technique for collecting legal materials in this research is library research. The legal material obtained is then processed using the syllogism method which uses a deductive mindset. Based on this research, research results were obtained which showed that the judge's consideration in deciding the case was in accordance with Article 363 paragraph (1) 4th and 5th of the Criminal Procedure Code and based on Article 183 and Article 184 of the Criminal Procedure Code. Criminal Procedure.